The role of next‐generation sequencing in the examination of signaling genes in Brca1/2‐negative breast cancer cases. (7th December 2022) - Cine, Naci; Ugurtas, Cansu; Gokbayrak, Merve; Aydin, Duygu; Demir, Gulhan; Kuru, Seda; Sunnetci‐Akkoyunlu, Deniz; Eren‐Keskin, Seda; Simsek, Turgay; Cabuk, Devrim; Aksu, Maksut Gorkem; Canturk, Nuh Zafer; et al.
Abstract: Introduction: Breast cancer is the most prevalent malignancy in women worldwide. Although pathogenic variants in the BRCA1/2 genes are responsible for the majority of hereditary breast cancer cases, a substantial proportion of patients are negative for pathogenic variations in these genes. In cancers, the signal transduction pathways of the cell are usually affected first. Therefore, this study aimed to detect and classified genetic variations in non‐ BRCA signaling genes and investigate the underlying genetic causes of susceptibility to breast cancer. Methods: Ninety‐six patients without pathogenic variants in the BRCA1/2 genes who met the inclusion criteria were enrolled in the study, and 34 genes were analyzed using next‐generation sequencing (NGS) for genetic analysis. Results: Based on the ClinVar database or American College of Medical Genetics criteria, a total of 55 variants of 16 genes were detected in 43 (44.8%) of the 96 patients included in the study. The pathogenic variants were found in the TP53, CHEK2, and RET genes, whereas the likely pathogenic variants were found in the FGFR1, FGFR3, EGFR, and NOTCH1 genes. Conclusion: The examination of signaling genes in patients who met the established criteria for hereditary breast cancer but were negative for BRCA1/2 pathogenic variants provided additional information for approximately 8% of the families. The results of the present study suggest that NGS is a powerful tool for investigating the underlying genetic causes of occurrence and progression of breast cancer.